Lack of association of rs3798220 with small apolipoprotein(a) isoforms and high lipoprotein(a) levels in East and Southeast Asians. Issue 2 (October 2015) - Khalifa, Mahmoud; Noureen, Asma; Ertelthalner, Kathrin; Bandegi, Ahmad Reza; Delport, Rhena; Firdaus, Wance J.J.; Geethanjali, Finney S.; Luthra, Kalpana; Makemaharn, Orawan; Pang, Richard W.C.; Salem, Abdel-Halim; Sasaki, Jun; et al.
Abstract: Objective: The variant allele of rs3798220 in the apolipoprotein(a) gene ( LPA ) is used to assess the risk for coronary artery disease (CAD) in Europeans, where it is associated with short alleles of the Kringle IV-2 (KIV-2) copy number variation (CNV) and high lipoprotein(a) (Lp(a)) concentrations. No association of rs3798220 with CAD was detected in a GWAS of East Asians. Our study investigated the association of rs3798220 with Lp(a) concentrations and KIV-2 CNV size in non-European populations to explain the missing association of the variant with CAD in Asians. Methods: We screened three populations from Africa and seven from Asia by TaqMan Assay for rs3798220 and determined KIV-2 CNV sizes of LPA alleles by pulsed-field gel electrophoresis (PFGE). Additionally, CAD cases from India were analysed. To investigate the phylogenetic origin of rs3798220, 40 LPA alleles from Chinese individuals were separated by PFGE and haplotyped for further SNPs. Results: The variant was not found in Africans. Allele frequencies in East and Southeast Asians ranged from 2.9% to 11.6%, and were very low (0.15%) in CAD cases and controls from India. The variant was neither associated with short KIV-2 CNV alleles nor elevated Lp(a) concentrations in Asians. Conclusion: Our study shows that rs3798220 is no marker for short KIV-2 CNV alleles and high Lp(a) in East and Southeast Asians, although the haplotype background is shared with Europeans. It appears unlikely that this SNP confers atherogenic potential on its own. Furthermore, this SNP does not explain Lp(a) attributed risk for CAD in Asian Indians. Highlights: rs3798220 is associated with long rather than short KIV-2 CNV alleles in Asians. rs3798220 variant alleles are not associated with high Lp(a) in these populations. This likely explains why this SNP in LPA is not associated with CAD in Asians.